Glycoproteins in cystic fibrosis: a lectin binding study. Issue 6 (December 1984) - Karlsson, S; Griffiths, B; Swallow, D M; Hopkinson, D A; Wallis, P G
Abstract : Ten lectins have been used to detect glycoproteins, after SDS polyacrylamide gel electrophoresis and gel isoelectric focusing, in fibroblasts, red cell membranes, urine, and plasma of patients and obligate heterozygotes with cystic fibrosis. No disease specific changes were detected but considerable individual variation was observed, some of which was attributed to known genetic polymorphisms unrelated to cystic fibrosis.